Chapter The Portuguese Montado: A Complex System under Tension between Different Land Use Management Paradigms - José, Muñoz-Rojas (InTechOpen, 2019)
The Montado is a silvopastoral system and the dominant land use in Alentejo (Portugal). Its functionalities expand beyond agricultural and forestry production. It is a system where a low-density and heterogeneous tree cover is complemented with livestock grazing and fodder production, resulting in its recognition as a high-nature-value farming system. However, for it to be effectively preserved, a balance between its many components needs to be secured. Despite the relevance and urgency of its conservation, the Montado has long suffered a constant decay. To better understand such decay, it is crucial to unravel why and how land use management decisions are made, and the interplay of drivers influencing such decisions. We applied discourse analysis to identify the various management paradigms that currently co-exist underpinning strategies by land managers and others. Our analysis is based on a review of the scientific literature, a media analysis, participant observations, and in-depth interviews with Montado farmers in Central Alentejo between 2014 and 2017, along with a survey with producers implemented during 2018. We conclude that existing strategies, and underpinning paradigms, are frequently incompatible, leading to the poor progress in halting the current decay of the system, and thus, also in securing its sustainability.